Antidiabetic Potential of Piper crocatum: A Systematic Review of In Silico, In Vitro, In Vivo, and Clinical Evidence - Nor, Islan; Padjrin, M. Awaluddin; Arsul, Muhammad Ikhlas; Julianti, Nurul Hasni; Abadi, Shada Adila; Haris, Tsurhaby (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2025)
Introduction: Diabetes mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia, affecting 463 million individuals worldwide in 2019. If inadequately controlled, DM leads to progressive and serious complications. Current management relies on oral antidiabetic agents and insulin therapy, but both are associated with adverse effects, driving interest in medicinal plants as complementary or alternative therapies. Piper crocatum (red betel), a tropical species widely cultivated in Indonesia, has long been used in traditional medicine and is increasingly recognized for its antidiabetic potential. Aims: This review critically synthesizes available evidence on the pharmacological effects of Piper crocatum in diabetes management. Method: Literature was systematically retrieved from Google Scholar using keywords “(Piper crocatum) AND ((Antidiabetic) OR (Antihyperglycemic))", screened through Covidence software, and evaluated according to PRISMA guidelines. Result: From an initial 500 records, 25 studies met the inclusion criteria. Findings from in silico, in vitro, in vivo, and clinical trials consistently support the glucose-lowering activity of Piper crocatum, highlighting it as a promising natural antidiabetic candidate. Conclusion: Future research should prioritize formulation development to enable downstream translation of Piper crocatum into Obat Herbal Terstandar (OHT) and Fitofarmaka.